Lokasi Optimal Pembangunan Pasar Tradisional di Kota Gunungsitoli Dengan Menggunakan SIG - Benhadad Solomasi Telaumbanua; Mussadun Mussadun (Department of Urban and Regional Planning, Faculty of Engineering, Diponegoro University, 2018)
Population growth in Gunungsitoli city has increased in the last 5 years. With the increasing of population growth, the need of market facilities to provide for the people also increases. Nevertheless, the market facilities in Gunungsitoli have not been increased. From the beginning there are only 3 traditional markets which located in the same districts while Gunungsitoli has 6 districts each quite far away from the others. Because of this situation, it needed to increase the number of traditional markets or improve the existing traditional markets. The purpose of this research is to determine the optimum location to build traditional market in Gunungsitoli city. The research method used is quantitative method with descriptive and spatial analysis with GIS. The results are Nou Market, Gomo Market and Soliga Market does not need additional market but need an extension, be renovated with additional facilities. Meanwhile for the 9 pekan need improvement such as local market development in every optimum location in Gunungsitoli Disctric Idanoi, South Gunungsitoli Distric, North Gunungsitoli District and Alo’oa Gunungsitoli Distric.